Developing architectural technologies for green buildings - Mandhyan, Akshita (Recent Research in Science and Technology, 2014)
It is experienced that present day people refer to ‘Green Technology’ with giving a very little thought to the environment. It has become more of a commercialization or branding gimmick. Green Technology aims at stepping into future, bringing out new innovations in hand with the nature, to curb the negative impacts of human involvement. Green technology ensures sustainability, waste reduction, innovation and viability. Introduction of Green technology into architecture has led to the birth of ‘Green buildings’. Green buildings do not just become ‘green’ by simple implementation of eco-friendly systems such as solar collectors, photovoltaic cells, biological recycling systems, building automation systems, etc into the building although these help but there’s more to it. There are various other factors which determine how ‘Green’ the building is! It includes everything, from the choice of building materials to be used for construction to its response to the environment around, the prevailing winds, temperature, humidity, sun paths and angles, etc. The wise use of these for natural light, ventilation, vegetation automatically reduces artificial energy consumption, thereby creating a ‘living building’. Architects should attempt designing buildings with eco-friendly materials, proper orientation, and thermal comfort. This research identifies the present context and suggests guidelines for architects/ planners to follow and develop eco-friendly environment.